Characteristics of patients with pseudochylothorax—a systematic review - Lama, Adriana; Ferreiro, Lucía; Toubes, María E.; Golpe, Antonio; Gude, Francisco; Álvarez-Dobaño, José M.; González-Barcala, Francisco J.; José, Esther San; Rodríguez-Núñez, Nuria; Rábade, Carlos; Rodríguez-García, Carlota; Valdés, Luis (Journal of Thoracic Disease; Vol 8, No 8 (August 01, 2016): Journal of Thoracic Disease, 2016)
Background: Pseudochylothorax (PCT) (cholesterol pleurisy or chyliform effusion) is a cholesterol-rich pleural effusion (PE) that is commonly associated with chronic inflammatory disorders. Nevertheless, the characteristics of patients with PCT are poorly defined. Methods: A systematic review was performed across two electronic databases searching for studies reporting clinical findings, PE characteristics, and the most effective treatment of PCT. Case descriptions and retrospective studies were included. Results: The review consisted of 62 studies with a total of 104 patients. Median age was 58 years, the male/female ratio was 2.6/1, and in the 88.5% of cases the etiology was tuberculosis (TB) or rheumatoid arthritis (RA). PE was usually unilateral (88%) and occupied greater than one-third of the hemithorax (96.3%). There was no evidence of pleural thickening in 20.6% of patients, and 14 patients had a previous PE. The pleural fluid (PF) was an exudate, usually milky (94%) and with a predominance of lymphocytes (61.1%). The most sensitive tests to establish the diagnosis were the cholesterol/triglycerides ratio (CHOL/TG ratio) >1, and the presence of cholesterol crystals (97.4% and 89.7%, respectively). PF culture for TB was positive in the 34.1% of patients. Favorable outcomes with medical treatment, therapeutic thoracentesis, decortication/pleurectomy, pleurodesis, thoracic drainage and thoracoscopic drainage were achieved in 78.9%, 47.8%, 86.7%, 66.6%, 37.5% and 42.9%, respectively. Conclusions: PCT is usually tuberculous or rheumatoid, unilateral and the PF is a milky exudate. The presence of cholesterol crystals and a CHOL/TG ratio >1 are the most sensitive test for the diagnosis. The lack of pleural thickening does not rule out PCT. Treatment should be sequential, treating the underlying causes, and assessing the need for interventional techniques.